Costa Rica: Achievements of a Heterodox Health Policy - Unger, Jean-Pierre (American Public Health Association, 2008)
Costa Rica is a middle-income country with a strong governmental emphasis on human development. For more than half a century, its health policies have applied the principles of equity and solidarity to strengthen access to care through public services and universal social health insurance. Costa Rica’s population measures of health service coverage, health service use, and health status are excellent, and in the Americas, life expectancy in Costa Rica is second only to that in Canada. Many of these outcomes can be linked to the performance of the public health care system. However, the current emphasis of international aid organizations on privatization of health services threatens the accomplishments and universality of the Costa Rican health care system.